2009
DOI: 10.4076/1752-1947-3-7312
|View full text |Cite
|
Sign up to set email alerts
|

Visor flap for total upper and lower lip reconstruction: a case report

Abstract: IntroductionNoma, aptly named the 'face of poverty', is a scourge with a mortality rate of up to 90% that affects some 140,000 people each year, predominantly children in the sub-Saharan 'noma belt'. Survivors of the acute attack suffer severe facial disfigurement from loss of facial tissue and scarring. Surgical reconstruction of noma defects is a major challenge, especially in Africa, where the majority of cases occur.Case presentationWe report the case of a 40-year-old Somali man who presented with severe f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…However, sacrifice of one major artery of the hand, numbness, and two obvious donor-site scars are the major disadvantages. Nthumba et al 4 have reported that a scalp visor flap can be applied to total lip defects. Its advantage is that it has an excellent blood supply via its double pedicle with two superficial temporal arteries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, sacrifice of one major artery of the hand, numbness, and two obvious donor-site scars are the major disadvantages. Nthumba et al 4 have reported that a scalp visor flap can be applied to total lip defects. Its advantage is that it has an excellent blood supply via its double pedicle with two superficial temporal arteries.…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports of reconstructing complete lip defects in the literature. 4,7,8 For repairing partial lip defects, a free RFA flap 5,6,9 has been the most frequently reported. It has the advantage of a good blood supply, but only a straight axial vessel is acquirable, which does not provide adequate coverage of the upper and lower lips.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multitude of local or pedicled flaps have been described to reconstruct total lip defects where free flaps are not an option but usually lack functionality or provide insufficient soft tissue, especially in younger patients with lack of skin laxity. The double mental neurovascular V-Y island advancement flap (Chen et al 2012;Fang et al 2014), the extended Karapandzic flap (Dediol et al 2018), the visor flap (Nthumba and Carter 2009), and the modified bilateral cheek flap (Chowchuen 2016) have been described and achieved good results, even though usually reserved for older patients after cancer resections, with more skin laxity. Furthermore, neck flaps can be used as salvage procedure in very sick or old patients who do not qualify for free tissue transfer or after failed free flap reconstruction (Yildirim et al 2010).…”
Section: Alternative Reconstructive Optionsmentioning
confidence: 99%
“…Cancrum oris is a disease that afflicts children, associated with poverty, malnutrition, poor oral hygiene and infectious disease; in adults, it has been associated with debilitating diseases such as HIV/AIDS, diabetes mellitus and hematological disorders. (Nthumba & Carter, 2009). With the advent of HIV/AIDS, noma appears to be on the increase: successful surgical reconstruction with minimal complications has been reported (Chidzonga & Mahomya, 2008).…”
Section: Plastic/cosmetic Surgerymentioning
confidence: 99%